Peri-operative management of neonates with oesophageal atresia and tracheo-oesophageal fistula. (June 2016) - Hunt, Rod W.; Perkins, Elizabeth J.; King, Sebastian
Summary: Oesphageal atresia is a relatively common congenital anomaly that requires urgent diagnosis, transfer to a neonatal surgical centre and management by a multidisciplinary team. Peri-operative management requires vigilant monitoring for the many possible associated morbidities. There are unique anaesthetic, airway and ventilatory considerations for this group of patients. Beyond the perinatal period, systematic neurodevelopmental follow-up is recommended to better understand the longer term outcomes for these children.